The Marketing Strategy of the Product with Sensual Marketing Reviewed from Islamic Perspective - Fajar Adhitya (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
There are many SPG who dress un−accordingly to the teachings of Islam when they are running product promotion activities. This study uses qualitative research method with a phenomenological approach. Subjects in this study were women who worked as SPG, while the research object was in Semarang City. The results of this study indicates that the use of Sales Promotion Girl is potential to violate Islamic Sharia because of the inadequacy of the clothes used by SPG, since in the marketing system, the clothes used by Sales Promotion Girl are considerate un−accordingly to the provisions of the Islamic Sharia or not in accordance with the perspective Islam.